2023
DOI: 10.1111/epi.17626
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic review of the effectiveness of psychological treatment of functional/dissociative seizures on non‐seizure outcomes in adults

Abstract: Functional/dissociative seizures (FDSs) are events characterized by alterations of awareness, self-control, and perception. [1][2][3] Although FDSs superficially resemble epileptic seizures, or in some cases syncope, they are not associated with epileptiform activity. FDSs are understood as an automatic response to internal or external triggers involving dysfunctional emotion regulation often occurring in the absence of conscious perception of adverse,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Others 31 have questioned whether another measure such as productivity might be more informative, and a recent meta-analysis has suggested that non-seizure outcomes are responsive to psychological treatment in patients with DS. 32 Given that CODES secondary outcomes showed between-group differences in 9 of 16 secondary outcome measures 10 11 it has also been questioned whether our primary outcome measure at 12 months post randomisation best represented the effectiveness of DS-CBT. 33 Discussion of outcome measurement in FND more widely 34 has advocated the use of core and supplementary measures.…”
Section: What We Did and What We Foundmentioning
confidence: 99%
“…Others 31 have questioned whether another measure such as productivity might be more informative, and a recent meta-analysis has suggested that non-seizure outcomes are responsive to psychological treatment in patients with DS. 32 Given that CODES secondary outcomes showed between-group differences in 9 of 16 secondary outcome measures 10 11 it has also been questioned whether our primary outcome measure at 12 months post randomisation best represented the effectiveness of DS-CBT. 33 Discussion of outcome measurement in FND more widely 34 has advocated the use of core and supplementary measures.…”
Section: What We Did and What We Foundmentioning
confidence: 99%